Naturalized athletes, symbolic representations of soft power through sports: Athletes naturalized in Japan and Korea, and Chinese athletes naturalized abroad - Cho, J.; Takamine, O. (2019)
In contemporary sports, naturalized athletes are active in a variety of countries and all types of games. Of course, an athlete becomes naturalized not only for sports but also after comprehensive consideration for many other reasons concerning life and life style. However, to analyze the societal background that leads to athletes making this decision is a realm of sociology. The analysis can explain the characteristics of the societies to which the athletes belong. Particularly in cases when athletes compete as the representatives of a country, such as the Olympics and world cups, they are the object of people`s enthusiasm, representing the identity of their state and nation. And the public`s acceptance or criticism of such athletes reflectsthat country`s social and cultural characteristics